A novel factor H-Fc chimeric immunotherapeutic molecule against Neisseria gonorrhoeae - Shaughnessy, Jutamas (J Immunol, 2016)
Neisseria gonorrhoeae (Ng), the causative agent of the sexually transmitted infection gonorrhea, has developed resistance to almost every conventional antibiotic. There is an urgent need to develop novel therapies against gonorrhea. Many pathogens, including Ng, bind the complement inhibitor factor H (FH) to evade complement-dependent killing. Sialylation of gonococcal lipooligosaccharide, as occurs in vivo, augments binding of human FH through its domains 18-20 (FH18-20). We explored the utility of fusing FH18-20 with IgG Fc (FH18-20/Fc) to create a novel anti-infective immunotherapeutic. FH18-20 also binds to select host glycosaminoglycans to limit unwanted complement activation on host cells. To identify mutation(s) in FH18-20 that eliminated complement activation on host cells, yet maintained binding to Ng, we created four mutations in domains 19 or 20 described in atypical hemolytic uremic syndrome that prevented binding of mutated fH to human erythrocytes. One of the mutant proteins (D to G at position 1119 in domain 19; FHD1119G/Fc) facilitated complement-dependent killing of gonococci similar to unmodified FH18-20/Fc, but unlike FH18-20/Fc, did not lyse human erythrocytes. FHD1119G/Fc bound to all (100%) of 15 sialylated clinical Ng isolates tested (including three contemporary ceftriaxone-resistant strains), mediated complement-dependent killing of 10/15 (67%) strains and enhanced C3 deposition (≥10-fold above baseline levels) on each of the five isolates not directly killed by complement. FHD1119G/Fc facilitated opsonophagocytic killing of a serum-resistant strain by human polymorphonuclear neutrophils. FHD1119G/Fc administered intravaginally significantly reduced the duration and burden of gonococcal infection in the mouse vaginal colonization model. FHD1119G/Fc represents a novel immunotherapeutic against multidrug-resistant Ng.